PELATIHAN PEMBUATAN KONTEN PROMOSI DIGITAL BAGI UMKM - Raja Tama Andri Agus; Muhammad Ardiansyah Sembiring; Mustika Fitri Larasati Sibuea (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
The rapid development of technology, the intense competition in the business world requires business actors to be able to keep up with the times. Content is currently very important in the business world to market products and services, so far many Usaha Mikro Kecil Menengah (UMKM) people are not aware of technological developments, especially in content creation. digital promotion for UMKM, people often complain and feel tired of doing their business, because it is difficult for them to market their products, for example there are those who sell food that doesn't run out and many other problems are felt by the community, thus making people lose and feel tired of doing business, therefore we want to make training in creating digital promotional content for UMKM, to make it easier for people, especially UMKM, to market their business in the digital world. For example, discussing strategies for creating content on social media, for example on TikTok, Instagram and creating their Google business profiles, so that their marketing reach is far more developed than before.